DONGENG MANUSIA LUAR BIASA: FOLKLOR LISAN “ISSUNBOUSHI: SANG KSATRIA MUNGIL” DAN “SI KELINGKING” (Super Ordinary Human Fairy Tales: Structural Analysis of “Issunboushi: Sang Ksatria Mungil” and “Si Kelingking”) - Inni Inayati Istiana; Ratna Asmarani; Sarwo Ferdi Wibowo; Mochammad Fikri (Kantor Bahasa Provinsi Sulawesi Tenggara, 2022)
This study examines two fairy tales from Japanese and Indonesian people namely the fairy tales “Issunboushi: Sang Ksatria Mungil” (Japan) and “Si Kelingking” (Indonesia) which have the same motif with different versions. This was done to answer the formulation of the problem in this study, how to compare the elements in the structure of the story which includes the similarities and differences in the story “Issunboushi: Sang Ksatria Mungil” with